Genome-wide analysis highlights contribution of immune system pathways to the genetic architecture of asthma - Yi Han (Nature Portfolio, 2020)
Asthma is a common disease of the airways for which numerous genetic loci have been identified. Here, Han et al. carry out a genome-wide analysis for asthma to identify additional loci, report sex-stratified and genetic risk score analyses, and functionally follow-up one locus using a murine model of airway hyperreactivity.